2015
DOI: 10.5935/0004-2749.20150040
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens explantation or exchange: indications, postoperative interventions, and outcomes

Abstract: Cataracts are one of the most common eye diseases associated with blindness (visual acuity worse than 20/400 in the better eye with best correction) worldwide, with an estimated 18 million people thought to be affected, and cataract surgery is the intraocular procedure performed most often worldwide. Over the years, the techniques of cataract surgery have evolved into a safe and successful procedure for visual rehabilitation. The incidence of most complications has significantly decreased with the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 14 publications
(20 reference statements)
2
19
0
3
Order By: Relevance
“…Incorrect lens power, patient dissatisfaction, and IOL opacification are common reasons for IOL replacement . Despite advances in biometry and IOL calculations, Behndig et al showed in a large analysis of Swedish cataract surgical outcomes that only two thirds of eyes planned for emmetropia become emmetropic .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incorrect lens power, patient dissatisfaction, and IOL opacification are common reasons for IOL replacement . Despite advances in biometry and IOL calculations, Behndig et al showed in a large analysis of Swedish cataract surgical outcomes that only two thirds of eyes planned for emmetropia become emmetropic .…”
Section: Discussionmentioning
confidence: 99%
“…Incorrect lens power, patient dissatisfaction, and IOL opacification are common reasons for IOL replacement. [1][2][3][4][5][6][7]9,10 Despite advances in biometry and IOL calculations, Behndig et al showed in a large analysis of Swedish cataract surgical outcomes that only two thirds of eyes planned for emmetropia become emmetropic. 13 While there are several options to correct residual refractive error after cataract surgery, including laser in situ keratomileusis, photorefractive keratectomy, piggyback IOLs and light-adjustable lenses, limitations and drawbacks exist for each technique.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study was conducted in 2015 to review the most common indications for AC explantation. Pseudophakic bullous keratopathy was the most common indication, accounting for 38.6% of the cases, followed by persistent iritis (27.8%), IOL decentration (13.6%), glaucoma (11.4%), refractive error (2.3%), and glare (2.3%) [9].…”
Section: Discussionmentioning
confidence: 99%